2002
DOI: 10.1086/338014
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Human Leukocyte Antigens and Nonresponsiveness to Influenza Vaccine

Abstract: Influenza remains a major cause of morbidity and mortality, particularly in at-risk groups where vaccination reduces complications of infection but is not universally protective. In order to determine whether human leukocyte antigen (HLA) class II polymorphisms modulate anti-influenza antibody responses to vaccination, a cohort of HLA-typed at-risk donors was investigated. The subjects were recruited from a single urban family practice. Hemagglutination-inhibition (HAI) titers were measured immediately before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 12 publications
3
79
1
Order By: Relevance
“…32,35 Indeed, HLA-associated vaccine failure has been reported for several vaccines. [36][37][38] In contrast to such reports, we found that non-HLA genes played a dominant role in Ab responses including total IgG in Gambian infants. These observations suggest that non-HLA genes exert a strong control on B-cell responses during the postnatal immune maturation process, whereas data from other studies in older population samples suggest HLA genes influence Ab responses triggered in immunologically mature individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…32,35 Indeed, HLA-associated vaccine failure has been reported for several vaccines. [36][37][38] In contrast to such reports, we found that non-HLA genes played a dominant role in Ab responses including total IgG in Gambian infants. These observations suggest that non-HLA genes exert a strong control on B-cell responses during the postnatal immune maturation process, whereas data from other studies in older population samples suggest HLA genes influence Ab responses triggered in immunologically mature individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…The two individuals that showed increases in MP response also had increases in HA responses, while the individual that did not show an increase in MP responses also did not have a HA response. These experiments were in line with a previous report that increases in humoral responses after influenza vaccination are only observed in 70% of the general population (15). This modest increase in CD4 ϩ T cell expansion is in marked contrast with the large oligoclonal expansions of CD8 ϩ T cells documented in many systems.…”
Section: Discussionsupporting
confidence: 92%
“…107 Some non-responsiveness to conventional influenza vaccines may be linked to MHC haplotype, suggesting that T-cell responses are a critical component of protective immunity in humans. 108 T helper response is also important to the control of influenza in mice. 105 It has been shown that in mouse models, lifelong CD4 responses to influenza are maintained.…”
Section: Correlates Of Protectionmentioning
confidence: 99%